Microwave-enhanced thermal processing of algae - Hong, Yu (2017)
Algae are promising substitutes to the widely-used fossil fuels. The thermochemical conversion of algae has been investigated extensively in the past two decades. In this study, systematic investigation of microwave-enhanced pyrolysis of algae together with catalytic reforming was conducted aiming at developing a new approach for the production of more syngas-enriched gas product from algae and other marine biomass. Firstly, the characterisation of algae was conducted to show the nature of the raw materials followed by the kinetic study of the decomposition of a suite of micro- and macro-algae, i.e., spirulina, chlorella and porphyra. The kinetic study was carried out using model algae, i.e. the use of ovalbumin as protein, oil droplets as lipid and cellulose as polysaccharides or carbohydrate to simulate a real alga. The thermogravimetric characteristics of algal samples were studied based on the analysis of TG and DTG curves. Kissinger-Akahira-Sunose method was used to derive the activation energy and pre-exponential factor. Moreover, the optimal reaction mechanism was determined by using Coats-Redfern method of the decomposition of different samples. The morphology and composition of char after TG analysis were characterised by using SEM/EDS. By comparing the characteristics of chars prepared in N2 and CO2 atmosphere, it was found that CO2 atmosphere favored the pyrolysis of algal protein with lower required activation energy (about 235 kJ mol-1) and shortened the pyrolysis time by 5.9-20.2%. But it was also found that the algal lipid increased the difficulty for the pyrolysis of algae with relatively higher activation energy around 200 kJ mol-1 (>180 kJ mol-1 under N2). However, the activation energy of cellulose decomposition remained almost the same around 310 kJ mol-1 in N2 and CO2. Therefore, CO2 atmosphere is more suitable for the pyrolysis of algae with high protein content and low lipid content. It was also found that protein in algae decomposes first, which is followed by the decomposition of carbohydrates and then lipids. Secondly, in order to obtain a high yield of syngas-enriched gas product from algae, microwave-enhanced pyrolysis of algae (spirulina, chlorella, dunaliella, laminaria and porphyra) and primary model algal compounds, i.e. cellulose and ovalbumin, at 400, 550 and 700°C in N2 atmosphere was conducted. The distribution and composition of gaseous, liquid and solid products were also studied in detail. Amongst the five algae, porphyra is the most promising raw material for high syngas-enriched gas production with more than 85 wt.%, while protein-rich spirulina and chlorella favored bio-oil production which yielded in about 10 wt.%. Meanwhile, with 94 wt.% carbohydrate, dunaliella converted most of its carbohydrates into C1-C3 gases. With a high portion of incombustible components (14.7-23.3 vol.% of CO2), laminaria has relatively lower gaseous production which was less than 80 wt.%. It also found that the optimal pyrolysis temperature was in the range of 400 to 550 °C for most of the samples except for spirulina which was at 700 °C. For the production of bio-oil, microalgae, with high protein content, were favored to be the raw materials (oil yield of 5.2-15.4 wt.%), compared to macroalgae (oil yield of 1.8-5.2 wt.%). Moreover, microalgae- spirulina and chlorella-favoured the formation of more phenols and nitrogenated compounds (10.8-17.8% and 20.9- 28.7% respectively) primarily from protein content, while less PAHs of 11.4-29.9% which mainly derived from algal carbohydrates. Finally, microwave-enhanced reforming of algae under CO2 atmosphere was conducted at 400, 550 and 700°C, together with the comparison of the results including the distribution and composition of gas, bio-oil and char in N2 and CO2 atmospheres. Compared with the product distribution derived under N2, the bio-oil yield from most algae in CO2 increased by 50- 170%, whilst the production of gas slightly decreased by 1-7%. Under CO2 atmosphere, the syngas in spirulina and chlorella gas product dramatically decreased by 60.8-69.7% and 7.1-17.6% respectively, while that from dunaliella increased by 23.4-30.4%. The percentage of syngas for the other samples remained similar. For the bio-oil derived from all the five algae samples, there were nearly no PAHs contained. In addition, the ash of algae was used as catalyst and introduced into the pyrolysis of five algae respectively under N2 atmosphere at 550°C. Compared with the non-catalytic pyrolysis, the weight percent of char from most algae increased by 20-90% using laminaria and porphyra ash, due to the decomposition of compounds in bio-oil. The syngas percentage from microalgae significantly increased by 6-45%, while that from macroalgae slightly decreased by 2-15% with the addition of spirulina, chlorella and porphyra ash. The content of PAHs in the bio-oil of spirulina, chlorella, laminaria and porphyra considerably reduced by 29-94%, while the amount of aromatics from spirulina and chlorella increased to around 1.3-7.1 times. In summary, the microwave-enhanced pyrolysis of algae favored the production of more CO/H2 rich gas at lower pyrolysis temperature under N2 atmosphere, while under CO2 atmosphere the yield of bio-oil increased. With the addition of algal ash as catalysts, the CO+H2 percentage in gas production from microalgae increased significantly. Therefore, it can be concluded that the microwave-enhanced pyrolysis of algae is an effective and efficient process for the conversion of algal biomass into value-added fuels.